Study of the Readiness of Specific Services for Senior High School’s Health Clinic in Jayapura - Meylani Aljeinie Tijow; Helen Try Juniasti (Journal of Educational Learning and Innovation (ELIa), 2024)
Senior High School (SMA) as an educational institution is responsible for ensuring the healthy environment that supports students' learning activities. However, in reality, the health of the school environment cannot be fully guaranteed. Various previous research studies have found various threats to the health of students originating from within the school environment, such as schools that are not yet free from cigarette smoke. The purpose of this study is to describe the current condition of the availability of School's Health Clinic facilities and infrastructure in high schools in Jayapura City and Jayapura District. The method used was descriptive quantitative approach with cross sectional design and Univariate Analysis. The research instruments refers to the minimum standard of Senior High School's health clinic according to the Regulation of the Minister of National Education of the Republic of Indonesia Number 24 Year 2007. The sample consisted of 32 public and private schools in Jayapura city and Jayapura district. The results showed that there was no extreme difference between the readiness of Senior High School's Health Clinic facilities and infrastructure in Jayapura City and District. However, public schools mostly have more adequate availability of Senior High School's Health Clinic facilities and infrastructure compared to private schools spread across the City and District areas.